Telehealth clinical learning: understanding pre-clerkship medical student experiences - Meera Anand; Sarah Wood (Canadian Medical Education Journal)
Background: With the onset of the COVID-19 pandemic, a reliance upon telehealth patient visits emerged. Many medical schools use early clinical experiences in the pre-clerkship years to provide opportunities to practice evolving clinical skills and broaden classroom learning. However, little is known about the value of telehealth visits during the pre-clerkship years. Therefore, the purpose of the current study was to determine what student learning experiences were with telehealth patient encounters during early clinical experiences.